Genetic diversity in potato (Solanum tuberosum L.) (Bangladesh Journal of Botany, 2008)
Genetic diversity in 31 potato genotypes (parents and their hybrid progenies) was determined using multivariate analysis. Cluster analysis revealed that the parents and their hybrid progenies could be grouped into five different clusters. The maximum number of genotypes were included in clusters II and V. Cluster V had maximum and cluster I had minimum intra-cluster distance. Cluster mean showed wide range of variation for several characters among single as well as multi-genotypic clusters. Considering diversity pattern, parents should be selected from clusters I, III and V for the improvement of potato. Â  Key words: Genetic diversity, Cluster analysis, Potato DOI = 10.3329/bjb.v36i2.1499 Bangladesh J. Bot. 36(2): 121-125, 2007 (December)